2015
DOI: 10.1007/s00411-014-0580-3
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of cancer incidence before the age of 15 years after exposure to ionising radiation from computed tomography: results from a German cohort study

Abstract: The aim of this cohort study was to assess the risk of developing cancer, specifically leukaemia, tumours of the central nervous system and lymphoma, before the age of 15 years in children previously exposed to computed tomography (CT) in Germany. Data for children with at least one CT between 1980 and 2010 were abstracted from 20 hospitals. Cancer cases occurring between 1980 and 2010 were identified by stochastic linkage with the German Childhood Cancer Registry (GCCR). For all cases and a sample of non-case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
139
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(152 citation statements)
references
References 27 publications
9
139
1
3
Order By: Relevance
“…14 Since the previously published risk analyses, [3][4][5][6][7][8][9][10][11][12][13][14] additional information on CT exposures and scan reports was collected for the period [2003][2004][2005][2006][2007][2008] in half of the participating hospitals and the follow-up (diagnosis of cancer, vital status) was extended up to 31 December 2010. Available information for scans performed before 1995 was sparse and not included in this report.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Since the previously published risk analyses, [3][4][5][6][7][8][9][10][11][12][13][14] additional information on CT exposures and scan reports was collected for the period [2003][2004][2005][2006][2007][2008] in half of the participating hospitals and the follow-up (diagnosis of cancer, vital status) was extended up to 31 December 2010. Available information for scans performed before 1995 was sparse and not included in this report.…”
Section: Data Collectionmentioning
confidence: 99%
“…Other cohort studies have found comparable results. [4][5][6][7] The interpretation of these results nevertheless requires an understanding of whether the excess risks of later malignancies observed after CT scans were due to the radiation exposure or to the underlying medical condition. 8,9 It is indeed possible that the increased incidence rates observed after receipt of CT scans were, at least in part, attributable to the indication for CT use, whether it was the first symptoms of a tumour, a followup for cancer predisposition or a non-cancer disease associated with an elevated risk of developing cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Claims that children are more sensitive to radiation and are more likely to get cancer from CT scans than adults are found repeatedly in many scientific articles (9,33,40,45,46,51). I do not know if these claims are true or not.…”
Section: The Use Of Ct Scans Has Grown Very Rapidlymentioning
confidence: 99%
“…In addition, there is variability in adherence to best practice clinical guidelines [30][31][32][33][34]. The issue of head CT and cancer risk is debated [35][36][37][38][39][40][41]; parental as well as emergency department providers' understanding of medical radiation exposure and cancer risk can vary [42][43][44][45]. Emergent care involves multiple stakeholders, including the patient and family, primary care physicians; nurses; emergency medicine physicians; trauma, pediatric and neurosurgeons; and the imaging team.…”
Section: Introductionmentioning
confidence: 99%